O uso da lectina de Parkia platycephala como moduladora da atividade antibiótica e no controle de nematóides gastrointestinais de ruminantes - SILVA, Romério Rodrigues dos Santos (2020)
Among the bioactive compounds present in plant organisms, there are lectins, proteins of nonorigin and their use is recognized in several biological activities, among them, antibacterial and anthelmintic. The use of natural products for this purpose has gained more notoriety due to the bacterial and helminth resistance to conventional drugs, commonly used in animal production. Among the organisms considered resistant to bacteria Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa are among the most frequent ones that affect farm animals causing serious infections such as mastitis, otitis, meningitis and abscesses, and helminths, Haemonchus contortus affecting small and medium-sized ruminants economic importance. In this context, this work aimed to evaluate the ability of a lectin from Parkia platycephala (PPL) to inhibit the development of H. contortus and modulate the antibiotic activity of gentamicin against multidrug-resistant strains of S. aureus, E. coli and P. aeruginosa. PPL did not inhibit the hatching of H. contortus eggs or larval drawing. However, it showed significant inhibition of larval development with an IC50 of 0.31 mg / mL. The MIC obtained for PPL against all tested bacterial strains was not clinically relevant (MIC ≥1.024 mg / mL). However, when PPL was combined with gentamicin, a significant increase in antibiotic activity was observed against strains of S. aureus and E. coli. The inhibition of hemagglutinating activity by gentamicin (MIC = 50 mM) revealed that this antibiotic interacts with the PPL carbohydrate binding site. The PPL-gentamicin interaction may be directly related to the increased antibiotic activity of gentamicin against strains of multi-resistant bacteria. PPL had an anthelmintic effect and modulated the antibiotic activity of gentamicin, which could be a new therapeutic resource against resistant bacterial strains and gastrointestinal nematodes.